Ask us! Adjusting experience‐based codesign to be responsive to people with intellectual disabilities, serious mental illness or older persons receiving support with independent living. (18th February 2022) - Heerings, Marjolijn; van de Bovenkamp, Hester; Cardol, Mieke; Bal, Roland
Abstract: Introduction: Experience‐based codesign (EBCD) is a valuable tool for participatory quality improvement. However, the EBCD process needs to be adjusted to make it suitable for long‐term care. The focus of the improvement process needs to shift to the care relationship, as this is an important part of the quality of care in these settings. Furthermore, the EBCD process needs to be made more accessible to vulnerable populations. Methods: Through a participatory research approach, EBCD was adjusted to long‐term care. The research was conducted in two care organisations: one supporting people with serious mental illness and intellectual disabilities in independent living and one providing homecare services for older persons. Results: The participatory research resulted in the development of 'Ask us!'—a method for critical reflective codesign. The research furthermore provided valuable lessons for participatory projects with vulnerable clients. A common problem with participatory research in long‐term care is ensuring the involvement of clients and informal carers. We report on various strategies developed to include experiences of a diverse set of services users, such as combining interviews with participant observation, photo‐voice and involving experts‐by‐experiences as co‐ethnographers. In close collaboration with an inclusive theatre company, these experiences were translated into 42 short videos on complex situations in the care relationship from the perspective of clients, professionals or informal carers. These videos instigate critical reflection and accelerate the participatory quality improvement process. Moreover, practical tools were developed to overcome barriers regarding the involvement of people with disabilities. These include the use of photo‐elicitation to enable participation of clients with disabilities in heterogeneous group discussions and involving experts‐by‐experience as proxies to share experiences of clients for whom participation in the 'Ask us' method remains inaccessible. Conclusion: The result of a robust participatory process, 'Ask us!' is a promising method for participatory quality improvement in long‐term care. The research furthermore generated lessons for involving vulnerable populations in participatory research and codesign. Patient or Public Contribution: Clients were involved as informants, sharing their experiences with the care relationship in interviews, photovoice and observations. They were also involved as consultants, helping to analyse input for the film scripts during data validation sessions.